Sustainable HRM and Employee Well-Being: Examining the Pathways to Retention and Organizational Resilience - Radha, P; Chandrasekar, Vidya; Vennila, R.; Lamichhane, Basu Dev (International Journal of Atharva, 2026)
Background: Organizations today face persistent uncertainty from economic volatility, digital disruption, and health-related shocks, making workforce stability and adaptive capacity strategic priorities. Despite growing interest in Sustainable Human Resource Management (S-HRM), there remains limited empirical understanding of how sustainable HR practices translate into retention and resilience, particularly through the mechanism of employee well-being. Objectives: This study aims to (1) examine the effect of S-HRM practices on employee well-being; (2) analyze the relationship between employee well-being and employee retention; and (3) test whether employee well-being mediates the relationship between S-HRM and retention, and how retention contributes to organizational resilience. Methods: A quantitative, cross-sectional research design was employed. Data were collected from 250–500 full-time employees across organizations using a structured questionnaire. Multiple regression analysis was conducted to test the hypothesized relationships, examining the direct and indirect effects of S-HRM practices, employee well-being, work-life balance, and perceived organizational support on employee retention and organizational resilience. A one-way ANOVA was also performed to compare well-being across groups. Findings: The results show that S-HRM practices (β = 0.31) and employee well-being (β = 0.28) significantly predict employee retention (R² = 0.56). Furthermore, S-HRM practices (β = 0.34), employee well-being (β = 0.29), and employee retention (β = 0.25) significantly predict organizational resilience (R² = 0.62). ANOVA revealed significant differences in employee well-being across groups (F(2, 87) = 14.50, p = 0.001). These findings confirm that employee well-being serves as a critical mediating pathway linking sustainable HR systems to both retention and resilience. Conclusion: This study concludes that S-HRM practices and employee well-being are pivotal drivers of employee retention and organizational resilience. Employee well-being functions not merely as an individual outcome but as a strategic organizational resource. By embedding well-being into HR systems, organizations can foster a stable, committed workforce that supports long-term adaptability and competitive advantage, demonstrating that investments in sustainable HRM are strategic enablers rather than cost centers. Originality: This study offers a novel contribution by empirically integrating S-HRM, employee well-being, retention, and organizational resilience into a single framework. It clarifies the mediating mechanism of well-being and bridges micro-level employee experiences with macro-level organizational capability, addressing a critical gap in the literature where these topics have been examined separately.